Electorate redistricting for a single-member district plurality, two-ballot voting system: Taiwan’s electoral reform - Lin Pei-Chun; Cheng Chiu Edwin Tai (Yugoslav Journal of Operations Research, 2014)
In this study, we formulated a mathematical model for electorate demarcation in line with Taiwan’s electoral reforms, minimizing legislative seats for the main opposition party in Taipei City. The model is compared with historical election data to establish characteristics that are most contested and germane to the reform. Examination of the constituency demarcation for the Seventh Legislator Election ascertains that electorate demarcation can/can not be manipulated to create electoral advantage. Demonstrable evidence of a bias toward disproportionate representation in the single-member district plurality, two-ballot voting system ultimately attests the importance of scenario analysis before adopting new electorate systems.